Muslim responses to the challenges of modernity - Abdul Rahim, Adibah (2011)
Modernity has been posing serious challenges to the Muslim world and its society since the eighteenth century. However, these challenges took on more definite shape in the nineteenth and early twentieth centuries. The challenges were complex and covered all facets of Muslim life. This paper tries to explore how Muslims can respond effectively to those challenges posed by modernity, and what are the main responses of modernity formulated over the past century. The response to the challenges of modernity, in fact, may be considered as one of the characteristics of Islam as a religion that has always shown a living awareness of contemporary intellectual issues.